NATIONALISM IDEOLOGY: CRITICAL DISCOURSE ANALYSIS OF JOKO WIDODO’S SPEECH IN INDONESIAN PRESIDENTIAL ELECTION - Diah Merrita (University of Muhammadiyah Malang, 2021)
Nationalism is a crucial trait a leader must have, especially a leader of a nation. It sticks to the leader as the role model for his nation. This research aims at analyzing a number of propositions in Joko Widodo’s victory speech as the chosen president during 2019—2024 taken from online news media. Proposition analyses are conducted in order to gain a number of macro propositions and nationalism ideology. This research uses proposition theory proposed by Teun van Dijk (1980) and critical discourse analysis from Norman Fairclough (1992). The result of this qualitative research reveals 18 macro propositions and six nationalism ideologies such as leadership attitude which prioritizes citizen welfare, reflection as a visionary leader, competitive attitude towards other countries, focus on unity of nation, a leader carrying out improvement in several sectors, and a proud leader towards Indonesia. The result also reveals that the prepositions uttered are in line with the nationalism concept proposed by Smith (2010), such as self-awareness as a part of a nation, a part of nation development, social and political movements for the sake of nation, and put nation’s necessities as the main attention and promote well-being.